THE PROBLEM OF THE NEW VULNERABILITIES OF THE RUSSIAN SOCIETY - S. A. Kravchenko (Vestnik MGIMO-Universiteta)
In article the author analyzes the new vulnerabilities which have arisen as a result of the formation of the complex socium in modern Russian society. It is shown that these vulnerabilities bear with themselves new risks for the functioning of the society and its members. The author argues that self-sufficiency of the Russian society is in real danger. The following vulnerabilities are specifically considered: the dysfunctions of the self-sufficiency of the society; the uncontrollable openness generating specific risks; the complex socium comprising the immanent potential of accidents; the process of complication of the risks; social and cultural dynamics of civilizations, the nature of their interactions; the vulnerabilities for the human capital. The solution of the arisen problems the author seems on the ways of the formation of non-linear and humanistic thinking as an intellectual basis of the Russian cosmopolitan human capital. This thinking proceeds from the acceleration and the complication of the sociocultural dynamics, the interdependent integrity of the mankind. The increasing requirements to the qualitative characteristics of the human capital induce to that at its formation were put and decided not only pragmatic tasks, the aims of the accumulation of the humanistic potential in the human capital. Respectively, the formation of the general strategy of the new stage in development of Russia has to assume the active interaction of political elite with scientific community from which, in turn, the new theoretical and methodological tools, capable to cope with the arisen problems are demanded.